Broadening the toolset for stakeholder engagement to explore consensus over wolf management. (15th October 2021) - Marino, Agnese; Ciucci, Paolo; Redpath, Stephen M.; Ricci, Simone; Young, Juliette; Salvatori, Valeria
Abstract: Facilitating coexistence between people and large carnivores is critical for large carnivore conservation in human-dominated landscapes, when their presence impacts negatively on human interests. Such situations will often require novel ways of mediating between different values, worldviews and opinions about how carnivores should be managed. We report on such a process in an agricultural area of recent wolf recovery in central Italy where unsolved social tensions over wolf presence have radicalized opinions on either side of the wolf debate, resulting in a stalemate. Where previous mitigation policies based on top-down damage compensation have failed, we tested the potential for applying a participatory approach to engage different stakeholder groups in a dialogue aimed at sharing a deep understanding of the problem and co-creating potential solutions. We based our approach on the theory of meta-consensus, using a decision support tool known as Multi Criteria Decision Analysis (MCDA). Over the course of three months, we carried out five workshops with stakeholder representatives from farming, hunting and environmental associations, and one biologist. Stakeholders shared several objectives and agreed over many management interventions, including the management of free-ranging dogs, the implementation of damage prevention measures, and a damage compensation system suitable for farmers. The process facilitated agreement over actions aimed at improving relations between stakeholders and enhancing the state of knowledge on the issues at stake. Most importantly, we recorded positive social and relationship outcomes from the workshops, and observed a willingness from participants to engage in further discussions over disputed management preferences. Overall, we found MCDA to be a useful tool for laying the groundwork for further participatory and deliberative processes on wolf management. However, challenges ahead included the involvement of a larger number of representatives of different social sectors, and a simplification of the methodology which some participants found too complicated and time consuming. Highlights: Agonistic pluralism theory provides insights into coexistence with carnivores. Meta-consensus theory helps identify the goal of deliberation over wolf management. Multi Criteria Decision Analysis facilitates structured and peaceful dialogue. Stakeholder deliberation generates positive social and relationship outcomes. Stakeholders in conflict over wolf management actually share several objectives.